2018
DOI: 10.3390/ijerph15112513
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection at Primary Healthcare Level in Abha City, Southwestern Saudi Arabia: Is Type 2 Diabetes Mellitus an Associated Factor?

Abstract: Background: There is an increasing concern about the relation between hepatitis C virus infection (HCV) and type 2 diabetes mellitus (T2DM). The present study aims to determine the prevalence of HCV infection among T2DM patients and non-diabetic patients attending primary healthcare centers (PHCCs) in Abha city, southwestern Saudi Arabia, and to explore the possible association between T2DM and HCV infection. Methods: A cross-sectional study targeting a random sample of T2DM and non-diabetic patients attending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Lower prevalence (1.8%) of HCV has been reported among blood donors [24] and 0.2-2.6% range reported in different age groups in the general public [25,26]. The result from this study is consistent with findings from different studies that reported a higher prevalence of the range 3.3%-24.8% [1,3,7,14,17,20,27]. The high prevalence in this small population can be attributed to the fact that diabetic patients are immune-compromised and secondly these individuals are exposed to HCV infection since they undergo frequent exposure to medical interventions and instrumentation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Lower prevalence (1.8%) of HCV has been reported among blood donors [24] and 0.2-2.6% range reported in different age groups in the general public [25,26]. The result from this study is consistent with findings from different studies that reported a higher prevalence of the range 3.3%-24.8% [1,3,7,14,17,20,27]. The high prevalence in this small population can be attributed to the fact that diabetic patients are immune-compromised and secondly these individuals are exposed to HCV infection since they undergo frequent exposure to medical interventions and instrumentation.…”
Section: Discussionsupporting
confidence: 90%
“…Hepatitis C virus (HCV) infection and diabetes mellitus (DM) are two major public health problems that may coexist and cause increased morbidity and mortality rates worldwide [1][2][3]. HCV affects between 170-210 million people globally, of whom 80 million have chronic hepatitis infection with complications that can lead to cirrhosis, liver cancer, and chronic kidney disease [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is now reported that more than 170 M individuals are infected with HCV globally. [1][2][3][4][5][6][7] Approximately 3-4 million cases occur every year with a significant risk of progression to chronic liver disease, cirrhosis and hepatocellular carcinoma. 8,9 The Ministry of Health (MOH) in Saudi Arabia, reported 9000 new cases of viral hepatitis in 2007, in that 32% were HCV infections.…”
Section: Introductionmentioning
confidence: 99%